Kajian Model Hidrograf Akibat Perubahan Tataguna Lahan dengan Menggunakan Data Lapangan DAS Batang Air Dingin - Elvi Roza Syofyan; Amrizal Saidi -; Bambang Istijono -; Revalin Herdianto - (Jurnal Ilmiah Poli Rekayasa, 2016)
Heavy rains on Monday, 21/3/2016, which flushed the city of Padang, West Sumatra, causing floods and submerged thousands of homes at local residents. This time called the flooding the worst experienced by the region in recent years. Head of Logistics Emergency and Disaster Management Agency said flooding in Padang city West Sumatra at this time was the worst, because it contributes to soak the areas that usually never flooded. The purpose of the study is to look at changes in land use and hydrograph models of Batang Air Dingin watershed using field data.The results shows the change of  land use of Batang Air Dingin Watershed can decreased 1.57%  from 2011 to 2015. It due to the opening of new land. While shrub rose rose 0.70%, because was due of changes of forests that have not done processing. For an others using of the land  the number increase 1.75%. It due to changes of forests and shrubs into failure land.. As the runoff coefficient (C) does not occur any significant change that is from 0.443 into 0.445. Peak discharge calculated by the Nakayasu method 179.274 m3 / dt, was greater by Snyder method of 177.150 m3 / dt is caused no difference in the approach used.